Pengaruh partisipasi anggaran terhadap kinerja aparat pemerintah daerah melalui komitmen organisasi dan persepsi inovasi sebagai variabel intervening (studi empiris pada satuan kerja perangkat daerah kabupaten siak) - Nuriani '; Restu Agusti; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research aims to examine the budget participation empirical evidence on the performance of local government in Siak either directly or indirectly through the variables between organizational commitment and perceptions of innovation. The sample used this research using purposive sampling technique with a total of 129 respondents. The population was 45 SKPDs Siak. Methods of data analysis used in this study is the analysis path with the help of software SPSS Version 17.0.The results showed that the presence of a direct effect of budgetary participation on the performance of local government. Budgetary participation also directly affects organization commitment and perception of innovation. But, budgetary participation did not indirectly affect performance of local government via organizational commitment and perception of innovation as a variable invervening.Keywords: Budget Participation, Local Government Officials Performance, Organizational Commitment, Perception of innovation.